(untitled) (Research, Society and Development, 2022)
The aim of this study was to compare the effect of posts systems and the luting agent on bond strength. Thirty single-rooted bovine teeth were used. The specimens were randomly grouped into: Rely X Ultimate- shaped pin (ULT-M), ULT- accessory pin (ULT-A), ULT- Splendor SAP (ULT-S), Rely X U200 (U200-M), U200-A and U200-S. The specimens were sectioned (cervical, middle and apical thirds) and submitted to the push-out test using the universal testing machine EMIC DL200MF. The data obtained were submitted to the Kolmogorov-Smirnov test, and later to the analysis of variance (ANOVA), complemented by the Student-Newman-Kells (SNK) multiple comparison test. The proportions of the type of failure were compared using the Z test. The significance level was 5% for all tests. The interaction Rely-X U200 and Splendor SAP System was the only group with no statistically significant difference, in all thirds. With the use of the Rely-X U200, the modeled retainer performed better in the middle third. The lowest bond values were in the apical region. The use of accessory retainers promoted adequate values in the cervical and middle thirds. For Rely-X Ultimate, the modeled retainer had the lowest strength values. The same happened with the middle and apical third of the group with accessory pins. There is an influence of luting agents and posts systems on bond strength values. The failure pattern is directly related to the retention system*luting agents*root third interaction.